Involvement of Parents in Children with Special Needs Intervention - Farah Farida Tantiani (Universitas Negeri Malang, 2020)
Parents are an important factor in the intervention process of special needs children. Therefore, this article aims to describe parental involvement in the intervention that can be done to optimize the development of special needs children. The parents' involvement that was analyzed in this article based on two models of early childhood education that involve parents in the educational process, such as the Portage model and Jowonio School. Interventions carried for special needs children have been carried out since they were in their early childhood period so that it is quite relevant to use the early education model as an example of parental involvement in their children's interventions. The advantage of using the Portage model because this model uses a home-based approach so that children with special needs get a high intensity of intervention. The strength of Jowonio School is an individual program in intervening children with special needs. However, special time is still needed for counseling the parents of children with special needs in recognizing and controlling the emotions felt by caring for children with special needs.Keywords: special needs children; intervention; parental involvement; therapy center.